Perceptions of music students about the effects of loud music and protective practices - Rodrigues, Matilde (2015)
As with professional musicians, also students can be exposed to dangerous sound pressure levels in the course of their academic activity, which can result in hearing damages. However, there are very few studies focused on the problem of music students’ exposure to loud music, particularly about the students’ perceptions and behaviours. In view of this, this study attempts to analyse the perceptions of the students about loud music risks, as well as to characterize their preventive behaviours and health effects. To analyse this issue, a questionnaire was developed and applied to music students of a secondary school. 123 students participated in the study. The results showed that most of students perceive ensemble classes and group study as noisy. However, several students assessed the sound levels in the different classes and in the additional study as low or moderate. Brass and percussion were identified as the noisiest instruments and strings were perceived as producing low and moderate sound pressure levels. The results also showed that only a part of the students were concerned with the health effects related to the exposure to high sound levels and the majority reported do not use hearing protection, since they never tried to use it or they seen it as non-necessary. The findings of this study showed that music students are not entirely aware of the risks associated with the exposure to high noise levels in the course of their practice and a strategy to improve protective behaviours need to be implemented in the music schools.